WARNING OF VIETNAM’S FOREIGN DEBT CRISIS - Huu Nghi Phan; Le Hung Son; Bui Do Van; Thanh Dung Dang; Tung Nguyen Duy (Scientific Journal of Pedagogy and Economics, 2020)
. Every country needs domestic and foreign investment capitals. Each capital source has itsф advantages and disadvantages associated with different policies, mechanisms and management that are associated with the characteristics of each country’s economy and culture. Developing countries like Vietnam, foreign loans for economic development are very important, creating a driving force to promote domestic investment and improve the efficiency of public investment in general if this capital is managed. effective management and monitoring. The rapid increase in the size and proportion of foreign loans in our country is concerned by many organizations and individuals with mixed opinions that: Foreign debts are under control, not worrying but meaningful. The idea is that it is necessary to warn the foreign debt crisis. The main purpose of the study is to analyze the current situation of Vietnam’s foreign debt in the period of 1986- 2018 to see the management and situation of foreign loans of our country today, build a debt crisis warning model based on Vietnam’s macro data to calculate the probability of a crisis so that it can adjust Vietnam’s debt management and debt management strategy, and as well as supplement foreign debt assessment and management tools. The article uses a research method which is a quantitative research method through the construction of a binary Probit model to determine the probability of a foreign debt crisis with two aggregate variables, namely Macroeconomic indicators and financial index variables. Through analyzing the situation of foreign borrowing and repayment in Vietnam during 1986-2018, the study thereby points out the limitations and causes of ineffective use of foreign debt in Vietnam. Besides, the results of the warning model show that the external debt crisis can be predicted through two explanatory variables, namely macroeconomic index and financial index variables.